1985
DOI: 10.1159/000242151
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plasma Arginine Vasopressin during Transition from Fetus to Newborn following Minimal Trauma Delivery of Lambs and Goats

Abstract: Vasopressin in umbilical arterial and venous blood is high at delivery and may be important in the maintenance of arterial pressure and absorption of lung liquid. We used chronically instrumented near-term fetal lambs and goats to investigate the changes in plasma vasopressin that occur during perinatal cardiovascular transition following cesarean section without labor. Plasma arginine vasopressin was more than 5 times greater 15 min following birth than immediately prior to clamping the umbilicus, and it fell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…By contrast, the arterial pressure of unfed lambs at a similar time after birth was lower (21) or unchanged from soon after birth (17). Perhaps vigorous movement of the lambs within the sling during and after feeding and volume expansion secondary to absorption of colostrum (plasma volume was increased during D4) contributed to the increase in arterial pressure.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…By contrast, the arterial pressure of unfed lambs at a similar time after birth was lower (21) or unchanged from soon after birth (17). Perhaps vigorous movement of the lambs within the sling during and after feeding and volume expansion secondary to absorption of colostrum (plasma volume was increased during D4) contributed to the increase in arterial pressure.…”
Section: Discussionmentioning
confidence: 94%
“…However, even after cesarean section, lambs have elevated levels of ADH, plasma renin activity, AII, aldosterone, catecholamines, and atrial natriuretic peptide, particularly within the first hour (17,(21)(22)(23). In addition, cortisol levels increase toward the end of gestation (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have shown that umbilical cord [VP] increases at birth both in human infants (22-27) and newborn sheep (12,13,28). Values are greatest after spontaneous vaginal delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Values are greatest after spontaneous vaginal delivery. Previous studies showed that [VP] in lategestation fetal sheep averaged <10 pU/mL and increased up to 5-fold during spontaneous labor, with plasma concentrations in umbilical cord blood averaging 10-30 pU/mL (12,13,28).…”
Section: Discussionmentioning
confidence: 99%